PARTISIPASI AMNUS BANJARMASIN DALAM MENDUKUNG KEGIATAN FESTIVAL BUDAYA KONGRES BORNEO RAYA, UPAYA PEMULIHAN EKONOMI KOTA BANJARMASIN - Kamsariaty; Capt. Moch. Nurdin; Andri Ali Wardhana; Hidayati Desy; Akhmad Syahbudin; Irnita Rosaria Santi; Juhrani (Akademi Maritim Nusantara Banjarmasin, 2022)
AbstractImplementation is an activity that has been arranged in accordance with the program and objectives, with the existenceof a Cultural Festival as a show to introduce the culture of each region as a characteristic of clothing, dance, language,food, and others which aims to provide general information about culture. through the show. The Greater BorneoCongress is a large gathering with magnificent performances or performances for the general public that can be seen orwatched by the wider community, in which the large gathering is given permission from political, social, or professionalparties who join to carry out the grand cultural congress in Banjarmasin. Banjrmasin as the islands of Kalimantanwith the nickname Borneo, while Raya is in accordance with the tribe or cultural universe that is displayed from theirrespective regions.Keywords: implementation, culture, economy